2014
DOI: 10.1179/1743132814y.0000000399
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted hUCB-MSCs migrated to the damaged area by SDF-1/CXCR4 signaling to promote functional recovery after traumatic brain injury in rats

Abstract: Transplanted human umbilical cord mesenchymal stem cells (hUC-MSCs) have exhibited considerable therapeutic potential for traumatic brain injury (TBI). However, how hUC-MSCs migrating to the injury region and the mechanism of hUC-MSCs promoting functional recovery after TBI are still unclear. In this study, we investigated whether stromal cell-derived factor-1 (SDF-1) was involved in the hUC-MSCs migration and the possible mechanisms that might be involved in the beneficial effect on functional recovery. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 20 publications
(19 reference statements)
2
39
0
2
Order By: Relevance
“…The mechanism of action for agonists or antagonists may be more related to CXCL12-mediated effects than CXCR7. CXCL12 levels are increased in most pathological conditions that CXCR7 is overexpressed in, including tumors [112,113], rheumatoid arthritis [34,114,115], stroke [116,117], multiple sclerosis [118], traumatic brain injury [119][120][121] and obesity [48]. An exception is that decreased blood levels of CXCL12 are observed in Alzheimer's disease [122].…”
Section: Why Agonists Are Producing Hypothesized Antagonist Resultsmentioning
confidence: 99%
“…The mechanism of action for agonists or antagonists may be more related to CXCL12-mediated effects than CXCR7. CXCL12 levels are increased in most pathological conditions that CXCR7 is overexpressed in, including tumors [112,113], rheumatoid arthritis [34,114,115], stroke [116,117], multiple sclerosis [118], traumatic brain injury [119][120][121] and obesity [48]. An exception is that decreased blood levels of CXCL12 are observed in Alzheimer's disease [122].…”
Section: Why Agonists Are Producing Hypothesized Antagonist Resultsmentioning
confidence: 99%
“…SDF-1/CXCR4 signaling is involved in the migration and survival of MSC and plays an important role in angiogenesis ( Lund et al, 2014 ; Li et al, 2015a ; Ma et al, 2015 ). There is also evidence that the therapeutic effect of MSCs is in part owing to their abundant secretion of SDF-1 ( Tang et al, 2011 ; Ranganath et al, 2012 ; Hatzistergos et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the C-X-C motif chemokine ligand 12 (CXCL12) is a frequent triggering factor at the site of injury. It has been demonstrated that a subpopulation of MSCs expresses the C-X-C chemokine receptor type 4 (CXCR4) that binds to its ligand, the CXCL12, to mediate cell migration (Wynn et al, 2004;Ma et al, 2015). Aside from CXCR4, MSCs express other chemokine receptors, such as CCR1, CCR2, CCR4, CCR7, CCR8, CCR9, CCR10, CXCR1, CXCR2, CXCR3, CXCR4, CXCR5, CXCR6, and CX3CR1 (Sordi et al, 2005;Von Luttichau et al, 2005;Honczarenko et al, 2006;Ringe et al, 2007).…”
Section: Migration Toward Damaged Tissuesmentioning
confidence: 99%